Doing Business 2008 : Comparing Regulation in 178 Economies - International Finance Corporation (Washington, DC: World Bank, 2012)
Doing business 2008 is the fifth in a series of annual reports investigating the regulations that enhance business activity and those that constrain it. Doing business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 178 economies, from Afghanistan to Zimbabwe, and over time. Regulations affecting 10 stages of a business's life are measured: starting a business, dealing with licenses, employing workers, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts, and closing a business. Data in doing business 2008 are current as of June 1, 2007. The indicators are used to analyze economic outcomes and identify what reforms have worked, where, and why. The Doing business methodology has limitations. Other areas important to business-such as a country's proximity to large markets, the quality of its infrastructure services, the security of property from theft and looting, the transparency of government procurement, macroeconomic conditions or the underlying strength of institutions-are not studied directly by doing business. To make the data comparable across countries, the indicators refer to a specific type of business-generally a limited liability company operating in the largest business city.